Co‐occurring depression and insomnia in Australian primary care: recent scientific evidence. Issue 5 (15th August 2021) - Sweetman, Alexander; Lack, Leon; Van Ryswyk, Emer; Vakulin, Andrew; Reed, Richard L; Battersby, Malcolm W; Lovato, Nicole; Adams, Robert J
Summary: Depression and insomnia commonly co‐occur, resulting in greater morbidity for patients, and difficult diagnostic and treatment decisions for clinicians. When patients report symptoms of both depression and insomnia, it is common for medical practitioners to conceptualise the insomnia as a secondary symptom of depression. This implies that there is little purpose in treating insomnia directly, and that management of depression will improve both the depression and insomnia symptoms. In this review, we present an overview of research investigating the comorbidity and treatment approaches for patients presenting with depression and insomnia in primary care. Evidence shows that clinicians should avoid routinely conceptualising insomnia as a secondary symptom of depression. This is because insomnia symptoms: (i) often occur before mood decline and are independently associated with increased risk of future depression; (ii) commonly remain unchanged following depression treatment; and (iii) predict relapse of depression after treatment for depression only. Furthermore, compared with control, cognitive behaviour therapy for insomnia improves symptoms of both depression and insomnia. It is critical that primary care clinicians dedicate specific diagnostic and treatment attention to the management of both depression (eg, psychotherapy, antidepressants) and insomnia (eg, cognitive behaviour therapy for insomnia administered by trained therapists or psychologists through a mental health treatment plan referral, by online programs, or by a general practitioner or nurse) when they co‐occur. These treatments may be offered concurrently or sequentially (eg, insomnia treatment followed by depression treatment, or vice versa), depending on presenting symptoms, history, lifestyle factors and other comorbidities.